Optimization of the electron beam dump for a GeV-class laser electron accelerator. (October 2021) - Shi, T.; Sun, D.; Jovanovic, I.; Kalinchenko, G.; Krushelnick, K.; Kuranz, C.C.; Maksimchuk, A.; Nees, J.; Thomas, A.G.R.; Willingale, L.
Abstract: The advances of laser-driven electron acceleration offer the promise of great reductions in the size of high-energy electron accelerator facilities. Accordingly, it is desirable to design compact radiation shielding for such facilities. A key component of radiation shielding is the high-energy electron beam dump. In an effort to optimize the electron beam dump design, different material combinations have been simulated with the FLUKA Monte Carlo code in the range of 1–40 GeV. The studied beam dump configurations consist of alternating layers of high-Z material (lead or iron) and low-Z material (high-density concrete or borated polyethylene) in either three-layer or five-layer structures. The designs of various beam dump configuration have been compared and it has been found that the iron and concrete stacking in a three-layer structure with a thick iron layer results in the lowest dose at 1, 10, and 40 GeV. The performance of the beam dump exhibits a strong dependence on the selected materials, the stacking method, the beam dump thickness, as well as the electron energy. This parametric study provides general insights that can be used for compact shielding design of future electron accelerator facilities. Highlights: Shielding is optimized for dumping 1–40 GeV electrons from a laser-driven accelerator. Stacking of iron and concrete exhibits the best shielding performance. Various material combinations are simulated with the Monte Carlo code FLUKA. The optimization result is useful for designing compact accelerator facilities.